ANALISIS PELAKSANAAN DAN MAKNA TRADISI WULLA PODDU DALAM KEHIDUPAN SOSIAL BUDAYA MASYARAKAT KAMPUNG TARUNG, SUMBA BARAT - Helga Susanti Gadi; Hildigardis M. I Nahak; Lenny Sofia Bire Manoe (Yayasan Literasi Sains Indonesia, 2026)
Traditional rituals constitute an essential component of the cultural system of traditional societies, as they embody symbolic, social, and religious values that represent collective identity. This study aims to examine the implementation process and symbolic meanings of the Wulla Poddu tradition in the socio-cultural life of the Tarung Village community, Loli District, West Sumba Regency. The research employs a qualitative approach with a descriptive method, utilizing observation, in-depth interviews, and documentation involving customary leaders, ritual practitioners, and local community members. The findings indicate that the Wulla Poddu tradition is carried out through eight main stages, tauna marapu, toba wanno, deke kawuku, kaleisuna, massusara, mana’a, kallango, and lulli, which take place over a one-month period and are led by traditional authorities. Each stage contains symbolic meanings associated with reverence for ancestors within the Marapu belief system. Furthermore, the tradition encompasses religious, social, moral, and ecological dimensions that function to strengthen social solidarity, regulate community behavior, and maintain harmony between humans and nature. Functionally, Wulla Poddu serves as a cultural mechanism that sustains social integration and preserves the continuity of traditional values within the community.